2018
DOI: 10.1016/j.rmed.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Early life determinants of lung function change from childhood to adolescence

Abstract: In summary, rather few exposures in childhood were identified to have a significant impact on lung function growth between childhood and adolescence. Our data support previous study findings indicating that lung function development is influenced by factors before birth and in infancy, including second hand tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to evaluate the incidence of FAO in children and adolescents with asthma. Previous studies evaluated the abnormal patterns of lung function from childhood into adulthood, but they did not evaluate FAO 8–15 . Some studies have demonstrated that patients with asthma present patterns of reduced lung function during childhood, 10,12,13,15 while others have shown that reduced lung function occurs only during adulthood 8,9,11 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, this study is the first to evaluate the incidence of FAO in children and adolescents with asthma. Previous studies evaluated the abnormal patterns of lung function from childhood into adulthood, but they did not evaluate FAO 8–15 . Some studies have demonstrated that patients with asthma present patterns of reduced lung function during childhood, 10,12,13,15 while others have shown that reduced lung function occurs only during adulthood 8,9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare our results with those of previous studies in the literature because no previous study has evaluated the risk factors for FAO in children and adolescents. There is evidence that BMI, 11,15,30 age, 11,13 second‐hand smoke, 11,15 respiratory tract infection, 15 prematurity, 15 and corticosteroid dose 30 are the main risk factors for patterns of reduced lung function in children and adolescents with asthma. Our results are supported by previous studies with adults suggesting that frequent asthma exacerbation and severe asthma are risk factors for FAO in adults 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations